2013
DOI: 10.1371/journal.pone.0081324
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Allosteric Regulation of YfiN from Pseudomonas aeruginosa: Clues from the Structure of the Catalytic Domain

Abstract: Pseudomonas aeruginosa is responsible for a plethora of biofilm mediated chronic infections among which cystic fibrosis pneumonia is the most frightening. The long-term survival strategy of P. aeruginosa in the patients lungs is based on a fine balance of virulence vs dormant states and on genetic adaptation, in order to select persistent phenotypes as the small colony variants (SCVs), which strongly correlate with antibiotic resistance and poor lung function. Recent studies have coupled SCV with increased lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 60 publications
(122 reference statements)
3
72
0
4
Order By: Relevance
“…Purification of the DGCs from P. aeruginosa, i.e., (i) YfiN HAMP-GGDEF (cytosolic portion containing the HAMP-GGDEF domain), (ii) YfiN GGDEF (construct containing the GGDEF domain), and (iii) WspR, was performed as previously described (14,22).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Purification of the DGCs from P. aeruginosa, i.e., (i) YfiN HAMP-GGDEF (cytosolic portion containing the HAMP-GGDEF domain), (ii) YfiN GGDEF (construct containing the GGDEF domain), and (iii) WspR, was performed as previously described (14,22).…”
Section: Methodsmentioning
confidence: 99%
“…We performed the experiment with YfiN GGDEF , which is a more suit- able system for denaturation experiments than PleD or WspR, given that its oligomeric state is not nucleotide dependent (14). We found that the presence of excess compound 7 (100 M) does not affect the secondary-structure content and the overall stability of the protein, thus indicating that the observed inhibitory property of compound 7 with DGCs is not due to unspecific folding effects (see Fig.…”
Section: Virtual Screening For Identification Of Novel Pled Inhibitorsmentioning
confidence: 96%
See 3 more Smart Citations